Karakteristike magnetronske celice s ploščato elektrodo - Vesel, Alenka (Materiali in tehnologije, 2000)
Electric characteristics of magnetron cell, which will be used in our new sputter ion pump, are described. Experimental magnetron cell consisted of an anode cylinder of the diameter of 27 mm and the length of 36 mm. Inside the anode cylinder a rectangular cathode stick was located. A stabel electronic discharge was established in the crossed electric and magnetic fields inside the magnetron cell. The molecules were analysed in inelastic collisions with electrons and excellerated toward the cathode. We measured the resulting ion current against the anode voltage at different pressures and at different magnetic fields. It was found that the ion current was strongly dependent on the anode voltage, the magnetic field density and the pressure. In any< case, a well defined maximum was found on the I=I(U) curve, and it increased with the increasing magnetic field and pressure. The maximum ion current dependent approximately linearly on pressure in the range between ?$10^{-10}$? mbar and ?$10^{-8}$? mbar.
Keywords: magnetronska celica; električne lastnosti; visoki vakuum; vakuumske črpalke